Epicardial Fat Tissue: A Potential Marker for Coronary Microvascular Dysfunction - Waiel Abusnina; Ilan Merdler; Matteo Cellamare; Kalyan R. Chitturi; Abhishek Chaturvedi; Irwin M. Feuerstein; Cheng Zhang; Sevket Tolga Ozturk; Teshome Deksissa; Vaishnavi Sawant; Kassandra Lopez; Lior Lupu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Coronary microvascular dysfunction (CMD), which mimics symptoms of obstructive coronary artery disease, has significant prognostic implications. While epicardial adipose tissue normally has a protective role, increased epicardial adipose tissue is associated with inflammation and may contribute to CMD. However, a direct correlation remains unclear. We aimed to investigate this association. Methods and Results The CMDR (Coronary Microvascular Disease Registry) is a prospective, 2‐center registry that is enrolling patients with angina and nonobstructive coronary artery disease who underwent invasive hemodynamic assessment of the coronary microvasculature. Patients with chest computed tomography within 1 year of CMD evaluation were included. We measured epicardial fat volume (EFV) and calculated the EFV index. Logistic regression analysis was used to investigate the association between EFV and EFV index to CMD. Our study included 130 CMDR patients with associated chest CT; 35 were diagnosed with CMD. The CMD‐negative patients were younger than the CMD‐positive patients (58.52±11.97 versus 63.37±9.56 years; P=0.033), with numerically fewer women (64.2% versus 74.3%; P=0.279). Univariate regression analysis demonstrated a statistically significant association between EFV index and CMD diagnosis (odds ratio, 1.037 [95% CI, 1.014–1.063]; P=0.003), while no significance was observed for EFV (odds ratio, 1.006 [95% CI, 0.995–1.017]; P=0.292). Conclusions Our results suggest a strong association between EFV index (a significant risk factor) and the presence of CMD. Future studies involving larger cohorts are needed to confirm the association of epicardial adipose tissue with CMD and investigate therapeutic targets to prevent CMD. Registration URL: https://www.clinicaltrials.gov; unique identifier: NCT05960474.